Promosi Digital dan Pengembangan Wisata Danau Kumbara - Ashari, Zahra Nabila Putri; Tinambungan, Wirawati; Mulyana, Mulyana; Apriliana, Lika; Jofachri, Muhammad; Yani, Naufal Vigar; Prayogi, Wahyu Tri; Ahmad, Islamudin (ANDIL Mulawarman Journal of Community Engagement, 2024)
Kota Bangun III Village, Kota Bangun Darat District, Kutai Kertanegara Regency, is a village that has the potential for tourism development, namely Kumbara Lake. Kumbara Lake is hte result of post-mining land which was developed into a tourist destination for local communities. The lack of facilities at Kumbara Lake has caused the community’s attractiveness to decrease. Apart from that, the lack information regarding Kumbara lake tourism is one of the factors that causes people not to visit Kumbara Lake. Therefore, the 49th KKN of Universitas Mulawarman has designed several prorams, namely, digital promotion and development of Kumbara Lake tourism. The method implemented is by developing facilities and promotions that are distributed through social media. The results of some of these work programs have been carried out well. The public can see the promotions through social media and the output of the work programs implemented is in form of photo spots and promotions video.